Synopsis of the grasses of Oaxaca, Mexico - Pacheco Rivera, Darisol; Dávila Aranda, Patricia (Instituto de Ecología, A.C., 2004)
As a contribution to the knowledge of the flora of the state of Oaxaca, Mexico, a   revision of the grasses was undertaken. Herbarium specimens from the main herbaria in Mexico were examined, as well as those recently collected in the region. A data base was created in order to compile and organize the available information. The results obtained show a total of 141 genera and 528 of native, introduced and cultivated species of grasses. These numbers approximately represent 68.60% of the grass genera and the 46.76% of the grass species that are present in Mexico. At the subfamily level the distribution of taxa is as follows: Centothecoideae (2 genera and 5 species); Arundinoideae (3 genera and 21 species); Bambusoideae (16 genera and 35 species); Pooideae (34 genera and 76 species); Chloridoideae (30 genera and 141 species); Panicoideae (56 genera and 250 species).  The complete list of all the grass species registered for the state of Oaxaca is included.